THE EFFECT OF FINTECH USE AND DIGITAL MARKETING ON THE FINANCIAL PERFORMANCE OF MSMES IN SUKASIRNA VILLAGE, CIBADAK DISTRICT, SUKABUMI REGENCY - Zemi Maulidi Niansyah; Hesri Mintawati; Yuli Dian Rahmawati (RADJA PUBLIKA, 2026)
he digital era has transformed the business landscape for Micro, Small, and Medium Enterprises (MSMEs), particularly through the adoption of financial technology (fintech) and digital marketing. Sukasirna Village in Cibadak District, Sukabumi Regency, has significant MSME potential but still requires in-depth study on the impact of digital technology on business financial performance. This research aims to analyze the influence of fintech and digital marketing usage on the financial performance of MSMEs in Sukasirna Village, both partially and simultaneously, and to identify moderating factors in this relationship. This research uses a quantitative approach with a survey design. The study population consists of MSME actors in Sukasirna Village who have used fintech and/or digital marketing for at least one year. Data was collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS software to test the causal relationships between variables. This research is expected to produce an empirical model that demonstrates the influence of fintech and digital marketing on the financial performance of MSMEs, and to provide strategic recommendations for optimizing the adoption of digital technology to improve the business performance of MSMEs in rural areas. The research findings can serve as a basis for decision-making for MSME actors in optimizing the use of digital technology, for local governments in formulating MSME digitalization policies, and for academics as a contribution to the development of technology adoption theory in the context of rural MSMEs.